Effect of laparoscopy on liver enzymes - Reddy, Prajyoth; Srinivasan, Siddharth; Rao, Akshay; Patil, Rajeev; Bansode, Pankaj H. (International Surgery Journal, 2020)
Background: Laparoscopic procedures have gained popularity in recent days because of advantages like small incision, less postoperative pain and discomfort, short hospital stay, early ambulation and early discharge. Very few studies are available to correlate Laparoscopic Surgeries and liver enzyme elevation. This effect may be due to either CO2 pneumoperitoneum, diathermy extruding liver, injury to branch of the hepatic artery or general anesthesia. This study was done to evaluate the changes in liver enzymes pre-operatively and post-operatively following laparoscopy. Methods: This prospective study included 103 patients who underwent various laparoscopic surgeries over a period of 2 years in Bharati Hospital & Research Centre, Pune, India. Serum AST, ALT and bilirubin levels were measured preoperatively and on post-operative day 1 and post-operative day 3. Patients with coexisting liver disease, Patients on long term use of hepatotoxic drugs, patients who developed complications such as CBD injury, obstruction, infection, leakage and high grade fever during surgery and in the post-operative period were excluded. Results: All laparoscopic procedures cause a transient elevation of serum bilirubin and liver enzymes. Elevation in the liver enzymes correlated directly with the duration of pneumoperitoneum. Elevation in the serum bilirubin but doesn’t correlates with the duration of pneumoperitoneum. These elevations do not have clinical significance in patients with normal hepatic function preoperatively. Conclusions: Duration of laparoscopic procedure should be kept to minimum and undue prolongation should be avoided. Decision to convert the operation to open surgery from a laparoscopic surgery should be prompt.